Air Pollution XX 2012
DOI: 10.2495/air120321
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of suspended particulate matter emitted from waste rice husk as biomass fuel under different combustion conditions

Abstract: There are large quantities of waste rice husk, e.g. around 3 million tons are estimated as biomass waste every year in Japan. Air pollutants emitted from exhaust gases of rice husk incineration lead to very important environmental damage, not only because of the influence on global environment and climate, when released into the atmosphere, but also on human health due to local air pollution. Therefore, it is necessary to effectively utilize waste rice husk and to reduce air pollutants. In recent years, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Christopher et al [55] reported a similar trend. Furthermore, Noaman et al [46] reported that the maximum tensile capacity occurred at the W/C of 0.5 in the specimen with 10% RHA. Considering the above, the pozzolanic features of RHA together with its filler role improves the tensile capacity.…”
Section: Tensile Strengthmentioning
confidence: 97%
See 1 more Smart Citation
“…Christopher et al [55] reported a similar trend. Furthermore, Noaman et al [46] reported that the maximum tensile capacity occurred at the W/C of 0.5 in the specimen with 10% RHA. Considering the above, the pozzolanic features of RHA together with its filler role improves the tensile capacity.…”
Section: Tensile Strengthmentioning
confidence: 97%
“…al. [46]. RHA was considered as the final output, and according to previous studies [20,25,32,34], it was used in concrete as a partial replacement of cement.…”
Section: Inventory Analysismentioning
confidence: 99%
“…From the above experiments, it was suggested that the reduction in the emissions of sulfur and chlorine contents [10] the combustion excretions could be achieved by carrying out combustion control with the help of char-biomass briquetting method. Based on the results of this study, more basic experiments have been carried out and different technologies were developed to control air pollutants emitted from biomass fuel, which were also reported in the 4th International Conference on Energy and Sustainability [11,12].…”
Section: Improvement On Combustion Experiments For Fi Xation Of Sulfurmentioning
confidence: 99%
“…As mentioned above, the behavior of harmful air pollutants emitted from rice husk and straw combustion were investigated by measuring carbonaceous and ionic composition of suspended particulate matter in PM 2.5 and the exhaust gases. It will be appreciated if the information of this study can be useful for production and application of small-size combustors [16] by using waste rice husk and straw or other biomass as fuel. The polycyclic aromatic hydrocarbons emitted from rice husk and straw combustion will be analyzed in further study to reduce the harmful air pollutants effectively.…”
Section: Carbonaceous Compositions Of Organic Substances (Oc) and Elementioning
confidence: 99%